Inclusive early childhood education and right of literacy even for children with disabilities - Malaguti, Elena (Form@re - Open Journal per la formazione in rete, 2017)
The literacy in the early childhood education has been considered through the perspective of inclusive education. The study highlights the importance of a strategic integrated approach to literacy, even direct to children with disabilities, promoting the full inclusion in the early childhood services and the bill of right communication. Educazione inclusiva per la prima infanzia e diritto alla lettura, anche per i bambini con disabilità La questione dell’apprendimento della lettura, per la primissima e prima infanzia, viene analizzata utilizzando la lente dell’educazione inclusiva. Lo studio suggerisce un approccio strategico integrato diretto ai bambini con disabilità, per promuovere la piena inclusione e il diritto alla comunicazione.